Developing a complex intervention to support timely engagement with palliative care for patients with advanced cancer in primary and secondary care in the UK: a study protocol. Issue 5 (14th May 2018) - Hackett, Julia; Bekker, Hilary; Bennett, Michael I; Carder, Paul; Gallagher, Jean; Henry, Claire; Kite, Suzanne; Taylor, Sally; Velikova, Galina; Ziegler, Lucy
Abstract : Introduction: For patients with advanced cancer, timely access to palliative care can improve quality of life and enable patients to participate in decisions about their end-of-life care. However, in a UK population of 2500 patients who died from cancer, one-third did not receive specialist palliative care, and of those who did, the duration of involvement was too short to maximise the benefits. Initiating a conversation about palliative care is challenging for some health professionals and patients often have unmet information needs and misconceptions about palliative care. We will work closely with patients and health professionals to develop a patient decision aid and health professional training module designed to facilitate a timely and informed conversation about palliative care. Methods and analysis: This study is being conducted over 24 months from November 2017 to October 2019 and follows the UK Medical Research Council framework for developing complex interventions and the International Patient Decision Aids Guideline. The Ottawa Decision Support Framework underpins the study. The Supporting Timely Engagement with Palliative care (STEP) intervention will be developed though an iterative process informed by interviews and focus groups with patients with advanced cancer, oncologists, general practitioners and palliative care doctors. An expert panel will also review each iteration. The expert panel will consist of a patient representative with experience of palliative care, health professionals who are involved in advanced cancer care decision-making, a medical education expert and the National Council for Palliative Care director of transformation. The feasibility and acceptability of the decision aid and doctor training will be tested in oncology and general practice settings. Ethics and dissemination: Ethical approval for the study has been granted by the Office for Research Ethics Committees Northern Ireland (ORECNI), approval reference 17/NI/0249. Dissemination and knowledge transfer will be conducted via publications, national bodies and networks, and patient and family groups.